The role of competitive amplification in explaining sustained performance heterogeneity - Wibbens, Phebo D. (Strategic Management Journal, 2021)
Research Summary This article introduces a formal model of long‐term resource dynamics under uncertainty. The model demonstrates the importance of competitive amplification for the emergence of sustained performance heterogeneity. In some markets, small differences in resource positions tend to amplify over time into large performance differences. The model predicts that this amplification and the resulting performance heterogeneity are largest in markets where firms compete for critical resources that are highly scalable, carry high sunk cost, depreciate rapidly and exhibit strong time‐compression diseconomies. Amplification emerges because in these markets an advantaged firm tends to have a stronger incentive to invest than a follower. Prior theories had paid little attention to the critical role of such competitive interactions in shaping long‐term resource dynamics. Managerial Summary In some markets, performance differences between competitors are much larger than in others. For instance, in high‐tech markets just one or a few firms tend to generate a large share of profits, while in utilities many different firms can exhibit similar performance levels. The mathematical model in this article suggests that the characteristics of the critical resources in a market play an important role in whether firms in that market will have similar versus very different performance levels. For instance, competition for resources that are not capacity‐constrained and depreciate rapidly—such as innovative technologies—tend to induce advantaged firms to extend their leads, which over time causes any small differences in resource positions to amplify into large performance differences. Conversely, capacity‐constrained and long‐lived resources—such as industrial plants—tend to induce attenuation of performance differences.